2005
DOI: 10.1681/asn.2004050387
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate of Perlecan Is Involved in Glomerular Filtration

Abstract: Perlecan is a heparan sulfate proteoglycan and a major component of the glomerular basement membrane. To understand the role of heparan sulfate chains of perlecan in glomerular filtration, detailed analyses were performed of the kidneys of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 38 publications
5
77
0
Order By: Relevance
“…While these recent data suggest that loss of heparan sulphate in the GBM alone does not lead to proteinuria, it is not clear whether loss of heparan sulphate under pathological conditions such as diabetic nephropathy accelerates or worsens proteinuria. An earlier study showed that loss of another heparan sulphate proteoglycan, perlecan, leads to proteinuria in albumin-overloaded perlecandeficient mice [38]. We speculate that loss of heparan sulphate may contribute to the pathogenesis of proteinuria under prolonged hyperglycaemic conditions.…”
Section: Discussionmentioning
confidence: 64%
“…While these recent data suggest that loss of heparan sulphate in the GBM alone does not lead to proteinuria, it is not clear whether loss of heparan sulphate under pathological conditions such as diabetic nephropathy accelerates or worsens proteinuria. An earlier study showed that loss of another heparan sulphate proteoglycan, perlecan, leads to proteinuria in albumin-overloaded perlecandeficient mice [38]. We speculate that loss of heparan sulphate may contribute to the pathogenesis of proteinuria under prolonged hyperglycaemic conditions.…”
Section: Discussionmentioning
confidence: 64%
“…Exon 3 deletion (Hspg2 3/3 ) viable: proteinuria after protein loading (Morita et al 2005); monocyte/macrophage influx impaired in Hspg2 3/3 Col18a1 2/ -mice in a model of renal ischemia/reperfusion (Celie et al 2007). Secreted as CSPG in some tissues (Danielson et al 1992;Govindraj et al 2002;Vogl-Willis and Edwards 2004;West et al 2006), but relationship of CSPG isoform to phenotypes not established.…”
Section: Hspg2mentioning
confidence: 99%
“…15,18 Mice lacking the attachment sites for HS on perlecan have normal glomerular ultrastructure and no renal disease but show increased susceptibility to protein-overload proteinuria. 19,20 Collagen XVIII mutants have mild mesangial expansion and only slightly elevated serum creatinine levels compared with controls. 21 Agrin has been identified as the predominant GBM-HSPG in all species studied, prompting speculation that it may be a critical determinant of the charge barrier.…”
mentioning
confidence: 98%